2011
DOI: 10.2209/tdcpublication.52.143
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Spoon Form for Feeding of Liquids in Infant Feeding Development

Abstract: Feeding development in infants is important not only for of the purpose of acquiring nutrition but also for developing the ability to intake liquids. Our previous study showed that the introduction of a straw was appropriate after an infant has acquired the ability to sip liquid from a spoon and/or cup. In this study, we investigated the effect of a bowlshaped spoon on liquid intake. The aim of this study was to determine the appropriate form of spoon for infant feeding development. Eleven healthy infants (3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…1). The teteo Cupspoon is hemispherical in shape, lets infants drink liquid from any direction, has a bowl width that is appropriate for an infant's mouth, and has a spoon size that corresponds to one mouthful for an infant [12]. Infants were free to choose their favorite beverage: water, tea, fruit juice, or isotonic beverage.…”
Section: Observationmentioning
confidence: 99%
“…1). The teteo Cupspoon is hemispherical in shape, lets infants drink liquid from any direction, has a bowl width that is appropriate for an infant's mouth, and has a spoon size that corresponds to one mouthful for an infant [12]. Infants were free to choose their favorite beverage: water, tea, fruit juice, or isotonic beverage.…”
Section: Observationmentioning
confidence: 99%
“…Lip movement during oral feeding can be visually observed. Several studies on the visual observation of lip movement during feeding have reported developmental progression of lip closure during bolus removal from a spoon or retention of a bolus within the oral cavity 8‐11 . Most of these studies have focused on spoon‐feeding with parental assistance.…”
Section: Introductionmentioning
confidence: 99%